Consumer protection and safeguards: proper information on the geographical origin of ingredients. The case of olive oils - Martínez Gutiérrez, Ángel; Vázquez Ruano, Trinidad (Przegląd Prawa Rolnego, 2021)
Since the nineties of the previous century, qualified geographic names have been covered by a harmonised EU-wide protection system whose main feature is the recognition of exclusive rights. Such rights are generally parallel to those deriving from the registration of a brand. Accordingly, they are not solely protected by the measures provided in the rules on unfair competition but also by a EU protection system based on granting the group of traders that had sought and obtained recognition of the protected designation of origin or geographical indication a monopoly over the use of a given geographic name and the possibility to seek remedy against any unlawful use of it. In this sense, the information provided generally benefits the market as well as merchants and consumers.